A Method Proposal To Determine Cruise Port Identity - Bayazit, Seyma; Kirval, Levent (International Review of Management and Marketing, 2018)
The purpose of this study is to propose a new method toward determining port identity for a cruise port. In this paper, the port identity concept is examined for the first-time under multi-criteria evaluation (MCE) approach as the port identity is composed with several criterions. Therefore, the proposed method includes two main steps. First is defining port identity and, is determining criteria which compose the port identity. Second is evaluating the criteria to determine port identity of a specific cruise port. To apply the proposed method, Bodrum which is a cruise destination, is selected as case study. Results are obtained by using Analytical Hierarchy Method (AHP). A survey study is conducted for pair-wise comparison of criteria. Participants are selected based on stakeholder analysis. The result determines the port identity for Bodrum by an 82.9 percentage stakeholder consensus. Local stakeholders prioritize port identity criteria historical-cultural (25.15%), natural (20.48%) and endemic (18.62%) places as the first three important criteria. Consequently, for destination managers and city planners, this paper reveals a common port identity concept as a decision making tool that can be used for future waterfront development strategies. Future studyies are expected to apply this new method for other cruise ports. Keywords: Port Identity, Cruise, Decision Making JEL Classification: Z310 https://doi.org/10.32479/irmm.6983